Impact of time to esophagogastroduodenoscopy in patients with nonvariceal upper gastrointestinal bleeding: A systematic review and meta-analysis - H.G. Bilder; C. Soccini; J.S. Lasa; I. Zubiaurre (Revista de Gastroenterología de México (English Edition), 2022)
Introduction: There is conflicting evidence regarding the benefit of urgent esophagogastroduodenoscopy (EGD) for reducing mortality and rebleeding, in the context of nonvariceal upper gastrointestinal bleeding. Aim: To describe the decrease in the risk for mortality, rebleeding, and red blood cell transfusion, with the performance of urgent EGD, in patients with nonvariceal upper gastrointestinal bleeding. Materials and methods: We carried out a search for cohort studies or controlled clinical trials, published from December 1966 to May 2020, that compared urgent EGD versus elective EGD in the management of adults with nonvariceal upper gastrointestinal bleeding, utilizing the MEDLINE, Embase, LILACS, and Cochrane Central Register of Controlled Trials databases. Our primary outcome was the hospital mortality comparison. The incidence of rebleeding and the mean number of red blood cell units transfused were also compared. A random effects model was utilized for the meta-analysis. Results: Twenty-one studies that met the eligibility criteria were included, involving 489,622 patients. We found no differences in the mortality of subjects exposed to urgent EGD versus elective EGD (RR 1.12 [0.72-1.72]). There was a significant increase in the risk for rebleeding (RR 1.30 [1.05-1.60]) in the subjects exposed to urgent EGD, and fewer red blood cell units were transfused in those patients (RR 0.52 [0.05-0.99]). Conclusions: Urgent EGD in subjects with nonvariceal upper gastrointestinal bleeding does not appear to have a significant impact on short-term mortality. Resumen: Introducción: Existen discrepancias en relación al beneficio de la esofagogastroduodenoscopía de urgencia para disminuir la mortalidad y el resangrado en el contexto de la hemorragia de tubo digestivo alto no variceal. Objetivo: Describir la reducción en el riesgo de la mortalidad, el resangrado y la transfusión de glóbulos rojos de la esofagogastroduodenoscopía urgente en la hemorragia de tubo digestivo alto no variceal. Materiales y métodos: Buscamos estudios de cohorte o ensayos clínicos controlados que comparasen la esofagogastroduodenoscopía de urgencia versus la esofagogastroduodenoscopía electiva en el manejo de sujetos adultos con hemorragia de tubo digestivo alto no variceal. Los estudios fueron identificados usando MEDLINE, Embase, LILACS y el Cochrane Register of Controlled Trials desde diciembre de 1966 hasta mayo de 2020. Nuestro desenlace primario fue la comparación de la mortalidad hospitalaria. Se compararon la incidencia de resangrado y el promedio de unidades de glóbulos rojos transfundidas. Para el meta-análisis, se utilizó un modelo de efectos aleatorios. Resultados: Se incluyeron 21 estudios que cumplieron con los criterios de elegibilidad y que involucraron 489,622 pacientes. No encontramos diferencias en la mortalidad de sujetos expuestos a esofagogastroduodenoscopía de urgencia versus electiva [RR 1.12 (0.72-1.72)]. Identificamos un incremento significativo del riesgo para resangrado [RR 1.30 (1.05-1.60)] y un menor número de unidades de glóbulos rojos transfundidas en sujetos expuestos a esofagogastroduodenoscopía de urgencia [RR 0.52 (0.05-0.99)]. Conclusiones: La esofagogastroduodenoscopía urgente en sujetos con hemorragia de tubo digestivo alto no variceal no impresiona tener un impacto significativo en la mortalidad a corto plazo.